IDENTIFICATION OF TALANG SEMUT AREA AS AN EUROPEAN ARCHITECTURE HERITAGE IN PALEMBANG CITY - Imam Sumarwoto (Universitas Indraprasta PGRI, 2023)
The Talang Semut area in Palembang City plays a central role as a region rich in history and cultural heritage, and is recognized as one of the oldest cities in Indonesia. Interactions with various cultures, including the strong influence of European architecture during the Dutch colonial period, have shaped the distinctive construction and spatial layout of Palembang City. The significant role of Dutch architects in this area further enhances its status as an invaluable cultural heritage site. Therefore, the aim of this research is to identify the Talang Semut area as a significant legacy of European architecture in Palembang City. The method employed in this study is a qualitative descriptive approach with both synchronic and diachronic perspectives. Data were collected from various sources, including direct observations, literature reviews, field surveys, and interviews with relevant informants. The research focuses on uncovering information about the evolution of the Talang Semut area from the past to the present, accommodating the changes and developments that have taken place. The results of this research are expected to provide a comprehensive understanding of the history and influence of European architecture in the Talang Semut area. The implications of this study go beyond enriching the cultural and historical insights of Palembang City, as it also contributes significantly to the preservation and safeguarding of existing cultural heritage and architecture. In other words, this research serves as a profound window into the cultural journey and spatial development of Palembang City, maintaining the connection between the past and the present.